Tell the machine goodnight - Williams, Katie, 1978- (Riverhead Books, 2018)
Pearl's job is to make people happy. Every day, she provides customers with personalized recommendations for greater contentment. She's good at her job, her office manager tells her, successful. But how does one measure an emotion? Meanwhile, there's Pearl's teenage son, Rhett. A sensitive kid who has forged an unconventional path through adolescence, Rhett seems to find greater satisfaction in being unhappy. The very rejection of joy is his own kind of "pursuit of happiness." As his mother, Pearl wants nothing more than to help Rhett--but is it for his sake or for hers? Certainly it would make Pearl happier. Regardless, her son is one person whose emotional life does not fall under the parameters of her job--not as happiness technician, and not as mother, either. Told from an alternating cast of endearing characters from within Pearl and Rhett's world, Tell the Machine Goodnight delivers a smartly moving and entertaining story about relationships and the ways that they can most surprise and define us. Along the way, Katie Williams playfully illuminates our national obsession with positive psychology, our reliance on quick fixes and technology. What happens when these obsessions begin to overlap?